The Influence of Organizational Culture and Organizational Commitment on Work Engagement at Pawnshops Sharia Sub-Branch Office in East Bandung Region - Mario Aldo Triadi Abidin; Egi Saepul Ahmad; Alvath Saemaria Noor (Research Collaboration Community (RCC), 2023)
The development of economic problems today, since the enactment of Law Number 10 of 1990, Islamic financial institutions not only consist of banks but also other Islamic financial institutions, namely non-bank financial institutions called sharia pawnshops. One of them is the Sharia Sub-Branch Office Pawnshop in the East Bandung Region which is a non-bank Islamic financial institution that helps the community in the economic sector. Organizational culture and organizational commitment at Pawnshop KCPS East Bandung Region greatly affect work engagement, which is one of the strongest factors of employees in deciding to stay or leave their jobs. The research method used is a quantitative method with an associative approach with primary data types and uses data collection techniques in the form of observations, interviews, literature studies, and questionnaires. Based on the results of the study, the number of employees at the KCPS Pawnshop in the East Bandung Region amounted to 34 people, which had the effect of b culture or organization to k attachment work with test results hypothesis that value tcount (3.797)Â > ttable (2,03693), there is an effect commitment organization to attachment work with results testing hypothesis that score tcount(15,122) > ttable(2,03693), and there is an effect of culture organization and commitment organization by simultaneous take effect to attachment work with test results Fcount(106,931) > Ftable(3,295).